Sex differences in genomics in lupus: girls with systemic lupus have high interferon gene expression while boys have high levels of tumour necrosis factor-related gene expression. (2nd September 2016) - Hui-Yuen, JS; Christiano, AM; Askanase, A
Abstract : Objectives : Systemic lupus erythematosus (SLE) is a chronic disease occurring up to 15 times more frequently in females than males. This bias extends to possible differences in disease flares and response to therapy. This study was initiated to investigate the differences between girls and boys with childhood-onset SLE (cSLE) at the molecular level. Method : We analysed the Gene Expression Omnibus National Center for Biotechnology Information (GEO NCBI) microarray data available for 88 girls and 16 boys with treatment-naïve cSLE and compared the results to those from healthy controls. Transcriptional profiles were generated using the platforms of Affymetrix U133A and U133B gene chips and Bioconductor/R programming packages were used to process and compare the data. Results : Girls with cSLE overexpressed an interferon (IFN)-α signature that was absent in boys. Boys with cSLE were observed to overexpress tumour necrosis factor-related genes that were absent in girls. Both boys and girls were observed to overexpress several genes related to granulopoeisis. Conclusions : Our results suggest a potential application of genomics to differentially predict response to therapy between females and males with SLE.